PENGARUH SARANA DAN PRASARANA DALAM MENUNJANG PRESTASI BELAJAR SISWA DI SD NEGRI 1 PANEMBAHAN - Indah Trihapsari; Roshyana Herawati; Nurkholis; Friska Widiyaningsih; Aghistya Rahmah; Nazwa Estu Auliya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The availability and proper management of educational facilities and infrastructure play a crucial role in supporting students’ learning achievement, particularly at the primary education level. This study aims to examine the influence of educational facilities and infrastructure on students’ learning achievement at SD Negeri 1 Panembahan. The research employed a quantitative approach using a causal associative method. The sample consisted of 45 students from grades IV, V, and VI, selected through a combination of purposive sampling and simple random sampling. Data were collected through observation and questionnaires and analyzed using descriptive and inferential statistical techniques. The results indicate that the condition of facilities and infrastructure at SD Negeri 1 Panembahan is generally categorized as adequate to good. The findings also reveal a positive and significant relationship between the quality of educational facilities and students’ learning achievement. However, the study identified a gap between the availability of facilities and their optimal utilization in the learning process. Therefore, effective management and innovative use of educational facilities are essential to maximize students’ academic potential and improve learning outcomes in primary schools.